Longitudinal Associations between Obesity, Inflammation, and the Incidence of Type 2 Diabetes Mellitus among US Black and White Adults in the CARDIA Study. (17th August 2020) - Jackson, Sharon H.; Bellatorre, Anna; McNeel, Timothy; Nápoles, Anna María; Choi, Kelvin
Abstract : Aim . Assess prospective relationships between obesity and inflammation on the incidence of type 2 diabetes mellitus (T2DM). Methods . A cohort of nondiabetic respondents from the Coronary Artery Risk Development in Young Adults (CARDIA) study was followed from 2005-2006 (wave 7) to 2010-2011 (wave 8). Diabetes status was determined in wave 8 based on self-report, blood glucose level, and anti-hyperglycemic medication use in conjunction with a homeostatic model assessment-based classification for distinguishing diabetes subtype. We performed a series of multivariable logistic regression analyses to assess the relative influence of obesity (waist circumference) and individual inflammatory biomarkers (i.e., C-reactive protein, fibrinogen, and sex-specific serum uric acid and gamma-glutamyltransferase) on the odds of developing incident T2DM between waves 7 and 8. Results . Among 2784 nondiabetic CARDIA respondents, 146 (5.2%) new cases of T2DM were identified between waves. Having a high waist circumference (AOR = 6.15 ; 95 % CI = 4.14, 9.14 ) and being Black (vs. White) (AOR = 1.60 ; 95 % CI = 1.05, 2.44 ) were associated with T2DM. Adjusting for inflammation biomarkers attenuated the effects of waist circumference and race with T2DM. Clinically elevated CRP (AOR = 1.83 ; 95 % CI = 1.18, 2.82 ) and uric acid (AOR = 2.57 ; 95 % CI = 1.70, 3.89 ) predicted T2DM among all respondents. However, stratification by race showed greater attenuation of the effects of waist circumference on T2DM in Whites than in Blacks when inflammation biomarkers were accounted for in the model. Conclusion . Targeted control of systemic inflammation may reduce the risk of developing T2DM, especially among Blacks, and could help address Black-White disparities in diabetes care and outcomes.